What does it mean to be visually literate? Examination of visual literacy definitions in a context of higher education. Issue 2 (3rd April 2018) - Kędra, Joanna
Abstract: Competency in visual literacy (VL) is crucial for effective visual communication, and thus for living and working in a visually saturated environment. However, VL across disciplines is still marginalized in higher education curricula. This tendency is partly caused by the lack of knowledge and agreement on what it means to be visually literate. This study juxtaposes and evaluates 11 VL definitions, selected as the most relevant for higher education practitioners and coined from 1969 (the first one) to 2013 (the most recent one). The study further proposes three lists of VL skills with thematic categories. Visual reading skills cover interpretation, analysis and understanding, visual perception, evaluation, knowledge of grammar and syntax and visual–verbal–visual translation. Visual writing skills cover visual communication, visual creation and image production and image use. Other VL skills include visual thinking, visual learning and applied image use. Additionally, the study indicates the types of visuals that can be used in visual education. It is suggested to close the debate over the concept of VL. Instead, based on the proposed lists of VL skills, a method of VL assessment can be created.